THEORETICAL ASPECTS OF ENGLISH LANGUAGE - Kasimova Adiba Nasirovna; Seytbekova Aynura (TADQIQOTLAR, 2025)
This article explores the nature, functions, and significance of stylistic devices and expressive means in the English language. The purpose of the work is to analyze how various linguistic tools enhance communication, influence readers and listeners, and contribute to the aesthetic and emotional tone of texts. The study highlights the role of figurative language, sound patterns, and syntactic structures as essential components of stylistic expression. It also demonstrates how understanding these elements improves the ability to interpret literary works and enhances overall communicative competence. The article is intended for students, researchers, and anyone interested in deepening their knowledge of English stylistics.